A scenario planning framework for (post-)pandemic tourism in European destinations. Issue 12 (2nd December 2022) - Seyitoğlu, Faruk; Costa, Carlos
ABSTRACT: Based on some presumptions or conditions to portray the future, scenario planning is a vital tool for scholarly evaluation of uncertainties and forming supportive strategies. Moreover, seeing that the course of the Covid-19 pandemic and the success of herd immunity is still not predictable, the world should be prepared for different future scenarios. In this vein, this study was designed to develop a scenario planning framework for the (post-)pandemic tourism in European destinations to make assumptions for the future and provide the necessary strategies. According to our scenarios, we suggest strategies comprising six main categories (financial strategies, travellers' expectations and confidence, coordination and collaboration, employment, (post-)pandemic tourism marketing, and sustainable (post-) pandemic tourism) for policymakers, destination managers, stakeholders, and practitioners in European destinations. To the best of our knowledge, this research is the first that presents a comprehensive scenario planning framework for (post-)pandemic tourism in European destinations. Thus, it can play a reference role in understanding the different circumstances and determining the specific strategies to recover or re-design the industry in the (post-)pandemic epoch.